6,7,8,9,10,11-Hexahydro-13H-azocino[2,1-b]quinazolin-13-one - Okmanov, Rasul Ya. (International Union of Crystallography, 2009)
The title compound, C(14)H(16)N(2)O, is a synthetic analogue of quinazolone alkaloids with pyrrilo, pyrido and azopino rings. The quinazolinic part of the molecule is generally planar within 0.037 (3) Å; the eight-membered ring exhibits an intermediate conformation between the chair and boat forms as it is typical for cyclooctene rings. An ethylene group of the azopino ring is disordered over two positions with a refined occupancy ratio of 0.910 (7):0.090 (7). In the crystal, the H atoms of the aromatic rings form weak C—H⋯O and C—H⋯N hydrogen bonds. One C—H⋯O hydrogen bond leads to the formation of a one-dimensional chain. Another C—H⋯O and a C—H⋯N bond link these chains, generating a three-dimensional network.